2009
DOI: 10.1079/pavsnnr20094044
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and control of enterotoxigenic Escherichia coli infections in pigs.

Abstract: Enterotoxigenic Escherichia coli (ETEC) are the most common bacterial cause of gastrointestinal disease and diarrhoea in the world, including travellers' diarrhoea and severe infection in some animal species, particularly calves and piglets. Many similarities exist between infections in animals and humans and extensive research has been done into the pathogenesis, prevention and treatment of ETEC infections. ETEC is an important infective agent in post-weaning diarrhoea (PWD) of piglets, leading to serious ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In previous work, we have shown that both enterotoxigenic Escherichia coli (an important causative agent of post-weaning diarrhoea) exposure and an increase in dietary crude protein (CP) level have a significant impact on ileal microbiota composition in weaner pigs, in the absence of changes at faecal level [ 1 ]. The manipulation of dietary CP levels has been considered as a control measure for post-weaning diarrhoea, as its reduction has been shown to lower disease severity [ 8 , 9 ]. In our previous work [ 1 ], we considered the spatial variation in the gut microbiota in response to dietary CP manipulation and enterotoxigenic Escherichia coli exposure but have yet to explore temporal changes in ileal microbiota composition.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have shown that both enterotoxigenic Escherichia coli (an important causative agent of post-weaning diarrhoea) exposure and an increase in dietary crude protein (CP) level have a significant impact on ileal microbiota composition in weaner pigs, in the absence of changes at faecal level [ 1 ]. The manipulation of dietary CP levels has been considered as a control measure for post-weaning diarrhoea, as its reduction has been shown to lower disease severity [ 8 , 9 ]. In our previous work [ 1 ], we considered the spatial variation in the gut microbiota in response to dietary CP manipulation and enterotoxigenic Escherichia coli exposure but have yet to explore temporal changes in ileal microbiota composition.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the economic losses associated with such diseases while avoiding the overuse of antimicrobial agents, the development of alternative management strategies needs to be considered (16). Dietary manipulation as a control measure for PWC has been considered due to previous evidence that reducing crude protein (CP) levels can lower disease severity (17, 18). Specifically, while amino acid supply from dietary protein is essential for a range of bodily functions, including maintenance, growth (protein deposition), and immune responses, when provided in surplus to digestive capacity, bacterial fermentation of excess protein and the resultant production of irritant, carcinogenic, and potentially toxic by-products such as ammonia, indole, cresol, and skatole can occur (19, 20).…”
Section: Introductionmentioning
confidence: 99%
“…After weaning in pigs, there is an increased risk for the development of enteric disorders such as postweaning colibacillosis. The symptoms that present as part of postweaning colibacillosis range from fecal shedding of enterotoxigenic Escherichia coli ( ETEC ) ( Fairbrother et al, 2005 ; Luppi et al, 2016 ) with no diarrhea to peracute fatal diarrhea ( Hodgson and Barton, 2009 ). The disease can be present at a subclinical level, whereby diarrhea is absent, but a variable reduction in performance may occur postweaning ( Hampson, 1994 ), which depending on its magnitude can clearly be of economic importance.…”
Section: Introductionmentioning
confidence: 99%